Analisis risiko pada Saham PT. Unilever Indonesia dengan metode expected shortfall berdasarkan model GBM with jump diffusion - Utami, Rossy Prima Nada; Haris, M. Al; Wasono, Rochdi (Jurusan Matematika FMIPA Universitas Jember, 2023)
Stock investment activities had a high level of profit and a high level of risk as well. The risk could be known from fluctuations in stock price data on stock returns. Fluctuations in stock price data on stock returns in each period could not be controlled, so predicting stock prices through returns was relatively difficult to do. The Geometric Brownian Motion (GBM) with Jump Diffusion model was proposed because it was able to capture fluctuations in stock return value data. The GBM with Jump Diffusion model was used when the data has extreme data or jumps that did not meet the assumption of normality, for example stock price data. This research was conducted to calculate the estimated risk of predicting the value of stock returns at PT Unilever Indonesia (UNVR) data for the period January 4, 2021, to January 27, 2023. Based on the results of the analysis, the estimated investment risk in UNVR stocks using the Expected Shortfall method showed that at a confidence level of 95% was generated a risk value of 0.05229, at 90% confidence level resulted in a risk value of 0.04436, at 85% confidence level resulted in a risk value of 0.03747 and 80% confidence level resulted in a risk value of 0.03645. So it could be said that the higher the level of trust, the higher the level of risk.Keywords: GBM, jump diffusion, PT Unilever Indonesia, expected shortfallMSC2020: 62P05, 91G70